(untitled) (Research Announcements "Heritage BG", 2025)
The study purpose is to detect the citizens’ culture forforest medicine and therapies related to the effect of a healthy lifestyle. Consumers’ opinions on innovative services were exploring: forest air and oxygen bath, forest art, forest menu, forest hammam and forest elephant eyes. The activities and publications of the Bulgarian Centre for Excellence ‘Heritage BG’ disseminate a multidimensional wellness culture. We present an analysis of applied psychometric experiment studying the importance, self-perception and satisfaction in communicating with forests and preserving them as natural heritage. References: Chipeva, Maya. Avangard Prima: Kango dzhémps Aerobika. Sofia, 2019. Dimitrova, Bistra, et al. Sotsialna znachimost na uelnes (wellness) kulturata: sravnitelen analiz po danni ot nauchni izsledvania na Galap interneshanal. Sofia, 2018. Dimitrova, Bistra, et al. Smart kognitiven instrumentarium. Vanshna otsenka na profesionalni kompetentsii za kadri v Nishov turizŭm. NSA Press. Sofia, 2021. Tomova, Tatiana. Menstrualni raztroĭ stva – razpostranenie i proyava. International Scientific journal Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 3, no. 2, 2021, pp. 33-38. Veselinov, Dimitar. Dialogat v obrazovanieto: Deseti mezhdunaroden esenen nauchno-obrazovatelen forum. Sofiya, 2021, pp. 11-16. Yosifov, Rumen. MMS: NSA ‘Vasil Levski’ Uchebna programa po sportna podgotovka za sportnite uchilishta – V–XII klas (Mart 2016 g. – Avgust 2016 g). 2019. Chalakov, Milen. "Optimizing the Control of Technical Performance of Forehand Stroke Among 12-year Old Tennis Players Using Martin’s Sigma method." Trakia Journal of Sciences, vol. 18, suppl. 1, 2020, pp. 682-688. Dimitrova, Bistra. "Quality assessment about standards for wellness services and certified skills of specialized staff." Trakia Journal of Sciences, vol. 17, no. 2, 2019, pp. 143-149. Dimitrova, Bistra. "Relationships between education and innovations in the recreational Industry in Bulgaria." Trakia Journal of Sciences, vol. 18, no. 2, 2020, pp. 143-149. Donev, Jordan, et al. "Comparative Study of Measuring Physical Activity Among Sport Students." International scientific congress ‘Applied sports sciences. Balkan scientific congress of physical education, sports and health’, 15-16 Nov. 2019, Sofia, Bulgaria. Ellis, Sussie. The global wellness tourism economy Report. GlobalWellnessTourism Congress, Global wellness institute, 2013, pp. 9-10. Global Wellness Institute. "Economic Report." 2014, pp. 27-28, www.globalwellnessinstitute.org. Accessed 3 Dec 2014. Harizanova, Olya. "New scientific infrastructure for innovations on the creative and recreative industries." Smart innovations in the Recreative & Wellness Industry and Niche Tourism Journal, no. 1, 2019, pp. 17-21. Ignatova, Darinka, and Alexandar Iliev. "MotorQualitiesandTheirInfluenceonChildren’sDevelopment." International Scientific Journal: Smart Innovations in Recreation, Wellness Industry and Niche Tourism, no. 2, 2020, pp. 16-44. Ivanova, Vessela. "Influence of Gymnastic Exercises in the Water Environment." International Scientific Journal: Smart Innovations in Recreational, Wellness Industry and Niche Tourism, no. 1, 2019, pp. 53-56. Konchev, Mihail. "Big Data, Neural Network and Predictive Analytics: Application in the Field of Sport." International scientific congress ‘Applied Sports Sciences’ and Balkan scientific congress ‘Physical Education, Sports, Health’, 2019, Sofia, Bulgaria, pp. 393-397. Nesheva, Irina. "Study of results between initial and final specific tests In women with normal pregnancy." Trakia Journal of Sciences, no. 17, suppl. 2, 2019, pp. 135-142. Nesheva, Irina. "Information systemforinclusion ofwomen withnormalpregnancy in gymnastics program." Smart Innovations on the Recreative & Wellness Industries and Niche tourism, no. 2, 2020, pp. 33-39. Polimenov, Mincho. "Transfer of Innovation in the Service Technology for Increasing the Restaurant Quality Product." International Scientific journal Smart Innovations in Recreational, Wellness Industry and Niche Tourism, vol. 1, no. 2, 2019, pp. 29-35. Trendafilov, Dimitar, and Bistra Dimitrova. "Aqua spinning as anti-stress health prevention." Sport Mont, vol. 11, no. 37-38-39, 2013, pp. 467-473.